A Green Route for Quick and Kilogram Production of Reduced Graphene Oxide and Their Applications at Low Loadings in Epoxy Resins. Issue 4 (25th January 2019) - Tiwari, Santosh K.; Nimbalkar, Ajaysing S.; Hong, Chang Kook; Ha, Sung Kyu
Abstract: This work reports a green and facile approach to produce bulk amount reduced Graphene Oxide using Graphene Oxide as precursor through Ball Milling in presence of Zinc (Zn) powder activated with NaOH (0.5 ml NaOH (1 M) for 2 g Zn powder). Compared to most of the reported reduction of GO by using hydrazine or any other means, the present route is quite simple, inexpensive and eco‐friendly. Since the proposed reduction for GO to rGO involves a solid‐state processing assisted with a friction and chemical reactions, no additional purification is required. Furthermore, the extent of reduction of GO (C/O ratio in rGO ∼8.8) in the present strategy is much higher than that in the different approaches using metallic Zinc and NaOH, indicating a cooperativity between friction generated during milling and chemical reactions. A probable mechanism for GO to rGO reduction is proposed and reduction strategy has been optimized in terms of milling time, rpm and amount of Zn powder used. To verify the applicability of as‐prepared rGO, we have examined the impact of rGO on the improvement of thermo‐mechanical and morphological properties of Epoxy nanocomposites. Here, few layered rGO based Epoxy nanocomposites were obtained via solution blending method and subsequent hot‐pressing. It was observed that rGO apparently filled in the interspaces of polymeric chains, which were helpful for the synchronously ∼10‐15% increment in thermo‐mechanical properties of fabricated nanocomposites even with an eminently low loading of rGO. Abstract : A commercial method to produce bulk amount reduced graphene oxide using Ball Milling strategy has been established. Produced reduced graphene oxide can be used for a wide range of applications and especially for the fabrication of polymer nanocomposites. To verify the applicability of the developed procedure, thermo‐mechanical properties of Epoxy nanocomposites with eminently low loading of rGO has been explored in details.